Contribution of milk production to food and nutrition security - Domínguez Salas, Paula; Galiè, Alessandra; Omore, Amos O.; Omosa, Esther B.; Ouma, Emily A. (Elsevier, 2019)
Milk is a nutrient-dense food product, which contributes importantly to healthy diets, especially of children and women, but also of adolescents and the elderly. The composition properties can vary during the production and processing procedures but remain of high nutritional value. Milk supply in low-and middle-income countries has been increasing over the past two decades in response to milk demand and consumption, and offers numerous pathways to enhance food and nutrition security of the most vulnerable populations.